Modelling India's External Sector: Review and Some Empirics. (November 2014) - Bhanumurthy, N.R.; Bose, Sukanya; Panda, Swayamsiddha
In the aftermath of the global food and fuel price spikes, and the recent global financial crisis, understanding of external sector behaviour has become crucial. The transmission mechanism of external sector shocks to domestic macroeconomic variables is essential for undertaking relevant policies to mitigate the adverse impact of such shocks. Here an attempt has been made to review the theoretical and empirical issues relating to India's external sector behaviour and to present a suitable analytical framework for macro modelling. JEL Classification: F4, C3